Soya Yoghurt Organoleptic Test With The Addition of Rosella Flower Extract - Rusyda Afifah; Amelia Nirmalawaty; Tiurma Wiliana Susanti Pandjaitan (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2022)
The unpleasant aroma of soy juice drinks causes not everyone to like it even though they know that the drink is healthy. Several studies have carried out efforts to overcome this condition, such as adding aromas, flavors, and fermentation. In this study, the effort to eliminate the unpleasant aroma was carried out through the fermentation process of soybean juice into soya yogurt accompanied by the addition of rosella extract. There are six levels of addition of rosella flower extract, namely from R0 (0%), R1 (10%), R2 (15%), R3 (20%), R4 (25%), and R5 (30%), with a fermentation process the same one. An organoleptic test was conducted on 30 selected panelists who like yogurt. The test uses a hedonic scale of 5 responses (very much like, like, quite like, dislike, and do not like). This study found that the addition of rosella flower extract eliminated the unpleasant aroma of soybean juice and the distinctive aroma of yogurt, thereby reducing consumer preference responses. The panelist's highest preference for color was in the R5 treatment. The addition of too much rosella extract concentration will cause the soy yogurt taste to be too sour, so the addition of rosella extract is recommended to be sufficient at 10% - 20%.